Социально-классовые позиции и ценностные ориентации - Патракова, А. (Социология: теория, методы, маркетинг, 2009)
The purpose of paper is to investigate the relationship between a class position and values orientations. At the first stage, the factor analysis was used for each of studied models. 1-st model includes 29 variables represents social orientations of respondents. 2-nd model dis plays a self-estimation / self-perception in 33 variables including 21 indicators developed by S.H.Schwartz. 3-rd model describes satisfaction with various aspects of life (11 variab les). There are compared value system structures of Ukrainian and Russian citizens, na mely: social orientations, a self-assessment / self-perception and satisfaction with life. At the second stage, the author has revealed by means of variance analysis some differences between Russia and Ukraine. Thus, in Ukraine, the higher is class position, the lower is the degree of anxiety and higher is the degree of a social acknowledgement, confidence in own forces, satisfaction both in life and in work. On the other hand, in Russia, the higher is class position, the higher is the degree of anxiety and the higher is social acknowledgement, as well as satisfaction both in life and work. Furthermore, the people occupying high class positions are characterized by such features, as un certainty in own forces, lack of self-confidence and need for self-affirmation.